"Spice" (Synthetic Marijuana) Induced Acute Myocardial Infarction: A Case Series. (26th July 2017) - Ul Haq, E.; Shafiq, A.; Khan, A. A.; Awan, A. A.; Ezad, S.; Minteer, W. J.; Omar, B.
Abstract : Marijuana is the most widely abused "recreational" substance in the United States, with highest prevalence in young adults. It is reported to cause ischemic strokes, hepatitis, anxiety, and psychosis. Although it is associated with dose dependent tachycardia and can lead to coronary vasospasm, it has not been directly related to acute myocardial infarction (AMI). Marijuana induced coronary vasospasm can result in endothelial denudation at the site of a vulnerable atherosclerotic plaque in response to hemodynamic stressors, potentially causing an AMI. Spice refers to herbal mixture with composition and effects similar to that of marijuana and therefore is referred to as "synthetic marijuana." Herein, we report 3 cases of spice induced ST-segment elevation myocardial infarction. All patients were relatively young and had few or absolutely no risk factors for cardiovascular disease. All patients underwent emergent coronary angiography, with two needing stent placement and the third requiring only aspiration thrombectomy. Our case series emphasizes the importance of suspecting and investigating synthetic marijuana use in low risk young adults presenting with AMI.